IMPROVEMENT CIRCUIT ENGINEERING OF MUTNOMETRII OF LIQUID OR GASEOUS MEDIA - E. I. Marukovich; S. S. Sergeev; A. P. Markov; K. Zakharova; A. G. Starovoytov (Литьë и металлургия)
Models and circuit realizations of information and transforming processes of optical-fibrous turbidimetry are considered.